Pengaruh Pelatihan K3 dan Kepemimpinan terhadap Perilaku Keselamatan Kerja pada PT. Trigunapratama Abadi - Dona Silviani; Citra Savitri; Wike Pertiwi (Journal Of Business, Finance, and Economics (JBFE), 2022)
Work safety is a crucial aspect within a workplace environment. In Indonesia, the awareness and compliance of employees towards safety practices are often lacking, resulting in a higher incidence of accidents that pose threats to the workers' well-being. This safety behavior is influenced by factors such as Occupational Health and Safety (K3) training and leadership styles. The aim of this research is to examine the impact of K3 training and leadership on work safety behavior. The study was conducted among 51 employees at PT. Triguna Pratama Abadi, utilizing a multiple linear regression method. The findings of the research reveal that K3 training has a partial effect on work safety behavior, as does the leadership factor. Furthermore, both K3 training and leadership collectively contribute to work safety behavior..